2014
DOI: 10.1371/journal.pone.0111072
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the Combined Effects of Chondroitinase ABC, Growth Factors and Locomotor Training following Compressive Spinal Cord Injury on Neuroanatomical Plasticity and Kinematics

Abstract: While several cellular and pharmacological treatments have been evaluated following spinal cord injury (SCI) in animal models, it is increasingly recognized that approaches to address the glial scar, including the use of chondroitinase ABC (ChABC), can facilitate neuroanatomical plasticity. Moreover, increasing evidence suggests that combinatorial strategies are key to unlocking the plasticity that is enabled by ChABC. Given this, we evaluated the anatomical and functional consequences of ChABC in a combinator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 61 publications
2
38
0
Order By: Relevance
“…When considering CST regeneration, however, the effects of chondroitinase have been less clear. Indeed, similar to our current results, a number of studies indicate that chondroitinase does not stimulate CST growth beyond complete spinal injuries, including complete transections spanned by transplanted tissue bridges (Fouad et al, 2005; Iseda et al, 2008; Alluin et al, 2014; Kanno et al, 2014). These findings, and the present results, are consistent with the notion that even in the presence of chondroitinase, severe spinal injuries present significant barriers to CST axon extension.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…When considering CST regeneration, however, the effects of chondroitinase have been less clear. Indeed, similar to our current results, a number of studies indicate that chondroitinase does not stimulate CST growth beyond complete spinal injuries, including complete transections spanned by transplanted tissue bridges (Fouad et al, 2005; Iseda et al, 2008; Alluin et al, 2014; Kanno et al, 2014). These findings, and the present results, are consistent with the notion that even in the presence of chondroitinase, severe spinal injuries present significant barriers to CST axon extension.…”
Section: Discussionsupporting
confidence: 88%
“…Although this response has occasionally been described as CST regeneration, it can be difficult in partial injury models to distinguish regeneration from sprouting (Tuszynski and Steward, 2012). Indeed, it is clear from numerous studies that CST axons respond to chondroitinase-mediated degradation of GAGs with increased sprouting of collateral arborization into spinal tissue (Alluin et al, 2014; Barritt et al, 2006; Garcia-Alias et al, 2009; Starkey et al, 2012; Zhao et al, 2011). Similarly, our results in the pyramidotomy injury model show clearly that lenti-chondroitinase promotes collateral sprouting of CST axons into denervated tissue (Figure 7), and it also appeared that in the crush model CST axons treated with Lenti-chase displayed increased collateral sprouting rostral to the injury (Compare Figure 6E,F to 6C,D).…”
Section: Discussionmentioning
confidence: 99%
“…If combined with treadmill exercise training, this effect is more significant [2]. Alluin et al showed that combination therapy of chondroitinase ABC, neurotrophic factors, and exercise training not only enhanced active motor function recovery by enhancing neuroanatomical plasticity of the descending tracts (corticospinal tract and 5-HT pathway) but also significantly reduced the astrocyte proliferation and inflammation around lesions [76]. Transplantation of Schwann cells and olfactory ensheathing cells in the spinal cord of cats combined with chondroitinase ABC treatment significantly improved motor function [77].…”
Section: The Effect Of Combinatorial Strategy With Exercisementioning
confidence: 99%
“…Unfortunately, SCI-induced disabilities that are observed in humans often are more substantial, which can limit the ability to translate treatments from animal models of SCI to clinically meaningful outcomes (Metz et al, 2000;Somers, 2000). In laboratories across the world, intervention strategies for SCI emphasize four major mechanisms for improving outcomes, including retraining motor abilities, replacing lost tissue, regenerating damaged connections, and/or retaining tissue from necrosis during the propagation of secondary injuries that occur following trauma (Alluin et al, 2014;Taylor, Jones, Tuszynski, & Blesch, 2006;Yasuda et al, 2011;Zendedel et al, 2012). Stem cell therapies show promise as a treatment after SCI in terms of providing trophic support, replacing lost cells, and regenerating functional neuronal architecture.…”
Section: Introductionmentioning
confidence: 99%